Impact of aircraft noise and language on primary school learners' reading comprehension in KwaZulu-Natal. - Kasimonje, Bahati M. (My University, 2013)
Today’s world is a fast developing world, with the transportation sector being one of the fastest developing sectors (Goldschagg, 2007). Through technologies such as an aircraft, one is able to travel across the globe in shorter periods of time. Unfortunately such progress often comes with environmental hazards; one such hazard being environmental noise (Stansfeld et al., 2005). However there has been little attention given to the effects of environmental noise, with much research focusing on aspects such as lead and air pollution on people’s wellbeing (Stansfeld et al., 2005). Yet environmental noise particularly aircraft noise is increasingly becoming an inevitable part of people’s world and has consequences on health, cognitive development and overall quality of life. Consequently this study investigates the impact of aircraft noise on a crucial component of learning (Reading Comprehension). Primary school learners in KwaZulu- Natal (N=834) scores on a test measuring Reading Comprehension (Suffolk Reading Scale2) were compared across a control group and an experimental group. Furthermore because Reading Comprehension involves language acquisition, in addition to investigating the impact of aircraft noise the impact of having English as an additional language on Reading Comprehension was also investigated. Learning in South Africa is predominantly facilitated in English while South Africa has eleven official languages with nine of them being indigenous languages. English for many learners may only be a second or even third language. Significant results were observed for both aircraft noise and language on reading comprehension as well as an interaction effect.
Keywords: Aircraft noise; Language; Reading comprehension; Kwa-Zulu-Natal